Assemblies, pressure measurement sheet set, sheet
Patent Information
- Application Number
- CN202180016469.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-25
- Filing Date
- 2021-01-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-01-26
AI Technical Summary
如专利文献1所记载的那样,上述片材在卷绕于卷芯的状态下进行运输和保存的情况较多
[0038]根据本发明,能够提供一种组装体,其具有卷绕于卷芯的片材,所述片材具有包含内含发色剂的微胶囊的层,即使在被施加由落下引起的冲击时,也抑制了微胶囊的破坏。
Smart Images

Figure CN115151499B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to assemblies, sheet assemblies for pressure measurement, and sheets. Background Technology
[0002] In recent years, due to the increasing functionality and sophistication of products, there has been a growing need to measure the distribution of pressure.
[0003] To determine the pressure distribution, a pressure measuring sheet assembly is known. This pressure measuring sheet assembly consists of a sheet having a layer containing microcapsules containing a color-developing agent and a sheet having a layer containing a color-developing agent. As described in Patent Document 1, these sheets are often transported and stored wound around a core.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-173307 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] On the other hand, in recent years, with the improvement of the color development characteristics of sheets, further attention needs to be paid to the processing of sheets. For example, if the sheet is subjected to impact, the microcapsules are easily damaged and cannot function as a sheet for pressure measurement.
[0009] The inventors evaluated the characteristics of an assembly comprising a roll of sheet material, which is obtained by winding a sheet material having a layer containing microcapsules containing a colorant, as described in Patent Document 1, onto a core. As a result, it was found that the microcapsules sometimes break when subjected to an impact caused by a hypothetical drop during transport and handling.
[0010] In view of the above-mentioned actual situation, the object of the present invention is to provide an assembly having a sheet wound around a core, the sheet having a layer containing microcapsules containing a colorant, which also suppresses the destruction of the microcapsules when subjected to an impact caused by falling.
[0011] In addition, the present invention also aims to provide a sheet assembly and sheet for pressure measurement.
[0012] Methods for solving problems
[0013] The inventors have conducted in-depth research on the above-mentioned problems and found that the above-mentioned problems can be solved by the following configuration.
[0014] (1) An assembly having:
[0015] core; and
[0016] A roll of the first sheet is formed by winding a long strip of the first sheet around a core.
[0017] The first sheet has a strip-shaped resin substrate and a first layer disposed on the resin substrate, containing microcapsules containing a color-developing agent.
[0018] The stiffness of the first sheet in the width direction is above 150mN.
[0019] (2) The assembly according to (1), wherein the stiffness of the first sheet in the width direction is greater than the stiffness of the first sheet in the length direction.
[0020] (3) The assembly according to (2), wherein the stiffness of the first sheet in the longitudinal direction is less than 180mN.
[0021] (4) The assembly according to any one of (J) to (3), wherein the stiffness of the first sheet in the width direction is 165mN or more.
[0022] (5) The assembly according to any one of (1) to (4) further comprises a pair of spacers disposed between the first sheets of the roll of the first sheet and disposed separately in the width direction of the first sheet.
[0023] (6) The assembly according to (5), wherein the thickness of the spacer is 1 to 5 mm.
[0024] (7) The assembly according to any one of (1) to (6), wherein the first sheet further has an adhesive layer between the resin substrate and the first layer.
[0025] (8) The assembly according to (7), wherein the sealing layer comprises a resin having repeating units derived from styrene or a derivative thereof.
[0026] (9) The assembly according to (7) or (8), wherein the thickness of the sealing layer is 0.01 to 2.0 μm.
[0027] (10) The assembly according to any one of (1) to (9) further comprises a pair of flange members fixed to both ends of the core.
[0028] (11) A sheet assembly for pressure measurement, comprising:
[0029] The assembly described in any one of (1) to (10); and
[0030] The second sheet has a second layer containing a color developer.
[0031] (12) A sheet assembly for pressure measurement, comprising:
[0032] A first sheet having a first layer comprising an elongated resin substrate and microcapsules containing a color-developing agent disposed on the resin substrate; and
[0033] The second sheet has a second layer containing a color developer.
[0034] The stiffness of the first sheet in the width direction is above 150mN.
[0035] (13) A sheet having a first layer comprising an elongated resin substrate and microcapsules containing a color-developing agent disposed on the resin substrate.
[0036] The stiffness of the first sheet in the width direction is above 150mN.
[0037] Invention Effects
[0038] According to the present invention, an assembly having a sheet wound around a core, the sheet having a layer containing microcapsules containing a colorant, which suppresses the destruction of the microcapsules even when subjected to an impact caused by a drop.
[0039] In addition, according to the present invention, it is also possible to provide a sheet assembly and a sheet for pressure measurement. Attached Figure Description
[0040] Figure 1 This is a perspective view showing one embodiment of the assembly of the present invention.
[0041] Figure 2 This is a perspective view showing one embodiment of the flange member.
[0042] Figure 3 yes Figure 3 A top view of the flange component.
[0043] Figure 4 This is a perspective view showing other embodiments of the flange member.
[0044] Figure 5 This is a cross-sectional view showing one embodiment of the first sheet.
[0045] Figure 6 yes Figure 5 Top view of the first sheet.
[0046] Figure 7 This is a magnified cross-sectional view of the first sheet. Detailed Implementation
[0047] The present invention will now be described in detail.
[0048] It should be noted that, in this specification, the numerical range represented by “~” refers to the range of values recorded before and after “~” as the lower and upper limits.
[0049] Furthermore, in the numerical ranges described in this specification, the upper or lower limit of a certain numerical range can be replaced with the upper or lower limit of other numerical ranges described in different stages. Additionally, in the numerical ranges described in this specification, the upper or lower limit of a certain numerical range can be replaced with the values shown in the embodiments.
[0050] The various components described below may be used alone or in combination of two or more. For example, the polyisocyanates described below may be used alone or in combination of two or more.
[0051] One characteristic of the assembly of the present invention is that the stiffness in the width direction of the first sheet wound around the core is adjusted.
[0052] The detailed reasons for achieving the desired effect by adjusting the above stiffness are not yet clear, but it is believed that when a collision occurs due to falling, if the above stiffness is above the specified value, even if an impact is applied to the first sheet roll, the deformation of the first sheet in the width direction is suppressed, thereby suppressing the deformation of the first layer, and as a result, the destruction of the microcapsules is suppressed.
[0053] Figure 1 This is a perspective view showing one embodiment of the assembly of the present invention.
[0054] The assembly 10 has a hollow cylindrical core 12, a pair of flange members 14 fixed to both ends of the core 12, and a roll 16 of the first sheet formed by winding the first strip-shaped first sheet (described later) around the core 12.
[0055] exist Figure 2 The middle shows Figure 1 A perspective view of the flange member 14 shown. Figure 3 The diagram shows a top view of the flange member 14. The flange member 14 has a base plate (flange) 18, an insertion portion 20 disposed on the base plate 18, and a protrusion 22 disposed on the surface (outer peripheral surface) of the insertion portion 20.
[0056] The insertion portion 20 of the flange member 14 can be inserted into the hollow portion of the hollow cylindrical core 12. Figure 1 In the middle, the insertion part 20 of the flange member 14 is inserted into the hollow part of the core 12, and the protrusion 22 of the insertion part 20 contacts the inner circumferential surface of the core 12, thereby fixing the core 12 and the flange member 14.
[0057] The following is a detailed description of each component.
[0058] <Curtain Core 12>
[0059] The first sheet is wound on the core 12.
[0060] Materials for the core 12 include plastic, paper, wood, and metal. Among these, paper is preferred from the perspective of being able to appropriately adjust the fixing strength between the core and the flange member. Examples of paper include paper tube base paper and resin-impregnated paper.
[0061] The size of the core 12 is not particularly limited, but the outer diameter (the diameter of the outer side of the core) is preferably 50 to 350 mm, more preferably 85 to 90 mm.
[0062] It should be noted that when the core is in a shape other than cylindrical, the aforementioned outer diameter is equivalent to the diameter of the circumcircle of the core.
[0063] The inner diameter of the cylindrical core 12 is preferably 45 to 345 mm, more preferably 80 to 85 mm.
[0064] It should be noted that, in Figure 1 In this embodiment, the core 12 is a hollow cylinder, but its shape is not limited by the implementation method as long as it can be wound around the first sheet.
[0065] For example, the core can be polygonal. Alternatively, the core can be solid.
[0066] <Flange Member 14>
[0067] Flange members 14 are fixed to both ends of the core 12. As described above, in Figure 1 In the middle, the core 12 and the flange member 14 are fixed by contacting the inner circumferential surface of the core 12 through the protrusion 22 in the flange member 14.
[0068] Materials for the flange member 14 include plastic, paper, wood, and metal. Plastic is preferred. Examples of plastics include polypropylene, polyethylene, and polyethylene terephthalate, with polypropylene being the most preferred.
[0069] It should be noted that the insertion portion 20 and the protrusion portion 22 described later are also preferably made of the aforementioned material.
[0070] The flange member 14 includes a substrate 18.
[0071] exist Figure 2 In this case, the substrate 18 is octagonal, but its shape is not particularly limited. It can be circular or other polygonal shapes other than octagonal (such as hexagonal).
[0072] The thickness of the substrate 18 is not particularly limited, but is preferably 1 to 50 mm, and more preferably 2 to 20 mm.
[0073] There is no particular limitation on the size of the substrate 18, but it is generally preferred to be larger than the outer diameter of the roll 16 of the first sheet. It should be noted that the size of the substrate 18 mentioned above refers to the diameter of the circumcircle of the substrate 18.
[0074] The size of the substrate 18 is preferably at least 1 mm larger than the roll 16 of the first sheet, more preferably at least 5 mm larger. There is no particular upper limit, but it is more common to be less than 600 mm.
[0075] The flange member 14 has an insertion portion 20 disposed on the substrate 18. The insertion portion 20 is a member that extends along the normal direction of the substrate 18.
[0076] The length of the insertion portion 20 along the extension direction is not particularly limited, but is preferably 2 to 100 mm, and more preferably 20 to 30 mm.
[0077] Figure 2 and Figure 3 The insertion part 20 shown is cylindrical, but it is not limited to this shape as long as it can be inserted into the hollow part of the core 12. For example, the shape of the insertion part can also be polygonal.
[0078] The outer diameter of the insertion portion 20 (the diameter of the outer side of the insertion portion 20) is preferably smaller than the inner diameter of the core 12. The outer diameter of the insertion portion 20 is preferably 45 to 345 mm, more preferably 80 to 85 mm.
[0079] A protrusion 22 is provided on the outer peripheral surface of the insertion portion 20. Figures 2-3 In this invention, the number of protrusions 22 is three, but there is no particular limitation on the number, and it may be four or more. From the perspective of further suppressing the destruction of microcapsules even when subjected to falling impacts (hereinafter also referred to as "the aspect of the invention that is more effective"), the number of protrusions 22 is three or more, more preferably four or more. There is no particular upper limit, and it is common for the number to be less than 100.
[0080] like Figure 3 As shown, three protrusions 22 are equally spaced on the outer peripheral surface of the insertion portion 20. The arrangement of the protrusions is not limited to... Figure 3 However, in the case of multiple protrusions, it is preferable that the multiple protrusions are arranged at equal intervals on the outer peripheral surface of the insertion part.
[0081] like Figure 3 As shown, the three protrusions 22 are arranged in contact with the substrate 18. The distance between the protrusions and the substrate is not limited to... Figure 3 The method is preferred, but it is preferable that the distances between the multiple protrusions and the substrate are all the same. That is, it is preferable that the distances between the protrusions and the substrate are the same for each protrusion.
[0082] exist Figure 2 and Figure 3 In the middle, the protrusion 22 is rectangular in shape, but its shape is not particularly restricted.
[0083] The height of the protrusion 22 (the height of the outer peripheral surface of the insertion part 20) is not particularly limited. It is sufficient to be the height at which the protrusion 22 contacts the inner peripheral surface of the core 12 when the insertion part 20 is inserted into the hollow part of the core 12. There is no particular limitation. Preferably, it is 0.1 to 5 mm, more preferably 0.5 to 2 mm, and even more preferably 0.5 to 1.5 mm.
[0084] It should be noted that the height of the protrusion can be constant or vary depending on its position. For example, in a more advantageous aspect of the invention, the height of the protrusion may decrease towards its end in a direction orthogonal to the direction in which the protrusion extends.
[0085] The width of the direction orthogonal to the direction in which the protrusion 22 extends is not particularly limited, but is preferably 1 to 25 mm, and more preferably 5 to 10 mm.
[0086] It should be noted that flange members are not limited to Figure 2 and Figure 3 The form, for example, such as Figure 4 As shown, a hole 40 can also be provided on the substrate 180 included in the flange member 140. By allowing a finger to pass through the hole 40, the assembly can be easily handled without falling. Figure 4 In the middle, the hole 40 is provided with 8 holes, but there is no particular limit to the number of holes; it can be 1 or more.
[0087] <Volume 1>
[0088] The first sheet roll 16 is a wound formed by winding the first sheet onto a core. The first sheet is long and narrow. Long and narrow means that its length in the longitudinal direction is longer than its length in the short direction.
[0089] Figure 5 A cross-sectional view in the width direction showing one embodiment of the first sheet. Figure 6 express Figure 5 Top view of the first sheet.
[0090] Figure 5 and Figure 6 The first sheet 24 shown has a support 26, an adhesive layer 28 disposed on the support 26, and a first layer 30 disposed on the adhesive layer 28. Figure 5 and Figure 6 In this case, a pair of spacers 32 are disposed on the first sheet 24. For example... Figure 5 and Figure 6As shown, a pair of spacers 32 are separately arranged in the width direction of the first sheet 24. In this manner, when the first sheet 24 is wound onto the core, the presence of the spacers 32 prevents the first layer 30 from contacting the support 26 located on the opposite side of the core side of the first layer 30, further suppressing the destruction of microcapsules in the first layer 30. Therefore, the assembly preferably also has a pair of spacers disposed between the first sheets of the roll of the first sheet, separately arranged in the width direction of the first sheet.
[0091] It should be noted that the above Figure 5 and Figure 6 The first sheet 24 shown includes an adhesive layer 28, but the invention is not limited to this method, and the first sheet may also not include an adhesive layer.
[0092] In addition, in the above Figure 5 and 6 The first sheet 24 shown is provided with spacers 32, but the present invention is not limited to this method, and the assembly may also not include spacers.
[0093] It should be noted that the stiffness in the width direction of the first sheet is 150 mN or more. For better performance of the invention, it is preferably 153 mN or more, more preferably 165 mN or more, further preferably 170 mN or more, and particularly preferably 175 mN or more. If the stiffness in the width direction of the first sheet is 165 mN or more, even in a first sheet having a first layer containing easily ruptured microcapsules corresponding to micro-pressures with color development below 0.2 MPa, the microcapsules are less likely to rupture. If the stiffness in the width direction of the first sheet is 175 mN or more, even in a first sheet having a first layer containing even more easily ruptured microcapsules corresponding to ultra-micro-pressures with color development below 0.05 MPa, the microcapsules are less likely to rupture. There is no particular upper limit, but values below 500 mN are common.
[0094] The stiffness of the first sheet in the longitudinal direction is not particularly limited, but from the viewpoint of better performance of the present invention, it is preferably 180 mN or less, more preferably 170 mN or less. The lower limit is not particularly limited, but from the viewpoint of manufacturing adaptability, it is preferably 100 mN or more, more preferably 130 mN or more.
[0095] In view of the superior effect of the present invention, the stiffness of the first sheet in the width direction is preferably greater than the stiffness of the first sheet in the length direction.
[0096] The ratio of the stiffness in the width direction to the stiffness in the length direction of the first sheet (stiffness in the width direction / stiffness in the length direction) is not particularly limited, and is often 0.90 or higher. However, for the sake of better performance of the present invention, it is preferably 1.00 or higher, more preferably 1.20 or higher, and even more preferably 1.22 or higher. There is no particular upper limit, but is often below 1.50, and even more often below 1.40.
[0097] The method for determining the stiffness mentioned above is as follows.
[0098] Test pieces with a length (longitudinal) of 200 mm and a width (transverse) of 15 mm were cut from the first sheet. The stiffness of the cut test pieces in the longitudinal and transverse directions was measured using a LOOPSTIFFNESS TESTER (manufactured by Toyo Seiki Co., Ltd.). The measurement conditions were set as follows: clamp spacing 100 mm, ring length 85 mm, and compression speed 3.3 mm / s. The above measurements were performed on two test pieces. The average of the length-direction stiffness obtained from the two test pieces was taken as the length-direction stiffness of the first sheet, and the average of the width-direction stiffness obtained from the two test pieces was taken as the width-direction stiffness of the first sheet. It should be noted that when measuring the length-direction stiffness of the first sheet, a test piece cut with the length of the test piece along the length of the first sheet was used; similarly, when measuring the width-direction stiffness of the first sheet, a test piece cut with the length of the test piece along the width of the first sheet was used.
[0099] It should be noted that the stiffness of the first sheet in both the width and length directions can be appropriately adjusted according to the type of components constituting the first sheet and the manufacturing method of the first sheet. For example, when the first sheet includes an adhesive layer, the stiffness of the first sheet can be adjusted by adjusting the thickness and number of layers of the adhesive layer, as well as the presence, type, hardness, size, and quantity of particles in the adhesive layer. In addition to the above, the stiffness of the first sheet can also be adjusted by adjusting the presence, type, hardness, size, and quantity of particles in the resin substrate. Furthermore, the stiffness of the first sheet can be adjusted by adjusting the stretching process during the manufacturing of the first sheet. Moreover, the stiffness of the resin substrate can be adjusted by adjusting the type of resin substrate used and the manufacturing conditions, and consequently, the stiffness of the first sheet can be adjusted.
[0100] The following is a detailed description of each component (resin substrate, sealing layer, first layer, spacer).
[0101] (Resin substrate)
[0102] The first sheet comprises a strip of resin substrate. The resin substrate is a component used to support the first layer.
[0103] Long strip-shaped resin substrates refer to resin substrates whose length in the longitudinal direction is longer than their length in the short side direction.
[0104] The width of the resin substrate is not particularly limited, but is mostly between 50 and 1500 mm, with 50 to 500 mm being the preferred width.
[0105] As a resin substrate, there are no particular limitations if the first sheet meets the specified stiffness characteristic. Examples include polyester films such as polyethylene terephthalate films, cellulose derivative films such as cellulose triacetate films, polyolefin films such as polypropylene and polyethylene, and polystyrene films.
[0106] The thickness of the resin substrate is not particularly limited, but from the perspective of better performance of the present invention, it is preferably 10 to 200 μm.
[0107] From the perspective of ensuring that the stiffness of the first sheet in the width direction is 150mN or more, and to ensure good transportability of the rolled sheet, the resin substrate preferably contains particles.
[0108] Examples of particles include inorganic particles such as calcium carbonate particles, calcium phosphate particles, silica particles, crystalline glass filler particles, kaolin particles, talc particles, titanium dioxide particles, alumina particles, silica-alumina composite oxide particles, barium sulfate particles, calcium fluoride particles, lithium fluoride particles, zeolite particles, molybdenum sulfide particles, and mica particles; and organic particles such as polystyrene particles, acrylic resin particles, methyl methacrylate particles, benzoguanamine-formaldehyde condensate particles, melamine-formaldehyde condensate particles, and polytetrafluoroethylene particles.
[0109] The resin substrate is appropriately selected in such a way that the first sheet exhibits the specified stiffness.
[0110] In addition, the stiffness of the resin substrate in the length and width directions can be adjusted by controlling the manufacturing conditions when manufacturing the resin substrate using a known method (extrusion molding).
[0111] The method for manufacturing the resin substrate may include a step of stretching the unstretched film (e.g., biaxial stretching). Furthermore, the method for manufacturing the resin substrate may include a heat setting step and a heat relaxation step. Additionally, the method described in paragraphs 0063 to 0125 of Japanese Patent Application Publication No. 2011-208125 may be used as the method for manufacturing the resin substrate.
[0112] As an example, the resin substrate in this invention is preferably free of coarse particles, foreign matter, defects, and precipitates. The number of coarse particles, foreign matter, and defects with a diameter of 5 μm or more is preferably 50 per 10 mm.2 The following is more preferably 10 per 10mm 2 the following.
[0113] (Sealed layer)
[0114] The adhesive layer is used to improve the adhesion between the resin substrate and the first layer.
[0115] From the perspective of further advantages of the present invention, it is preferable that the sealing layer is a resin layer containing resin, and it is also preferable that the capsule wall material of the microcapsule is made of resin, and the sealing layer is a resin layer containing resin. In particular, when the first layer contains a small amount of binder, the microcapsules sometimes aggregate together when the composition having microcapsules is coated and dried. If the sealing layer is a resin layer, then... Figure 7 As shown, the microcapsules 34 in the first layer 30 interact with the adhesive layer 28 on the resin substrate 26, thereby inhibiting the aggregation of the microcapsules 34. The microcapsules 34 can exist in a stable dispersed state on the adhesive layer 28, thus improving the color particle size during pressure measurement.
[0116] The material constituting the adhesive layer is not particularly limited, and examples include styrene-butadiene resin, styrene (meth)acrylic resin, (meth)acrylic resin, olefin resin, urethane resin, polyester resin, and polyvinyl alcohol resin. Among these, styrene-butadiene resin, styrene (meth)acrylic resin, or (meth)acrylic resin are more preferred from the perspective of better adhesion between the resin substrate and the first layer.
[0117] In particular, from the viewpoint of further enhancing the effects of the present invention, the sealing layer preferably comprises a resin having repeating units derived from styrene or its derivatives. Especially when the capsule wall material of the microcapsule has an aromatic structure, the color-developing granularity becomes better if the sealing layer also has an aromatic structure.
[0118] Resins having repeating units derived from styrene or its derivatives may contain repeating units other than those derived from styrene or its derivatives.
[0119] The content of repeating units derived from styrene or its derivatives in the resin is not particularly limited, but is preferably 5 to 100 by mass relative to all repeating units.
[0120] Styrene derivatives are compounds in which styrene is substituted with substituents (e.g., alkyl, alkoxy, carboxyl, or halogen atoms) at the α, ortho, meta, or para positions.
[0121] The thickness of the sealing layer is not particularly limited, but it is often 0.01 μm or more at the lower limit. From the perspective of better performance of the present invention, it is preferably 0.04 μm or more. It is often 5 μm or less at the upper limit. From the perspective of better performance of the present invention, it is preferably 3 μm or less. From the perspective of better color development granularity when used as a sheet for pressure measurement, it is more preferably 2.0 μm or less.
[0122] The sealing layer can be a single-layer structure or a multi-layer structure. When the sealing layer is a multi-layer structure, the overall thickness of the sealing layer is preferably within the range mentioned above.
[0123] In addition, the adhesive layer may contain materials other than the aforementioned resin. Examples of such materials include, for example, inorganic and organic particles. Examples of inorganic and organic particles include particles identical to those that may be contained in the resin substrate. The particles may be particles with antistatic properties. Furthermore, a variety of particles may be used, and they may be included in both the resin substrate and the adhesive layer.
[0124] From the perspective of further advantages of the present invention, it is preferable that at least one of the resin substrate and the adhesive layer contains particles. By including particles in at least one of the resin substrate and the adhesive layer, the stiffness of the first sheet in the width direction can be easily adjusted to 150 mN or more.
[0125] From the perspective of adjusting the stiffness of the first sheet in the width direction to 150 mN or more, it is preferable that the particle size contained in either the resin substrate or the adhesive layer is large. Specifically, the proportion of inorganic particles with a particle size of 1 μm or more in the total inorganic particles is preferably 50% by volume or more, and the proportion of inorganic particles with a particle size of 10 μm or more is more preferably 50% by volume or more.
[0126] When either the resin substrate or the adhesive layer contains inorganic particles and resin, the proportion of inorganic particles with a particle size of 1 μm or larger in the total inorganic particles and the proportion of inorganic particles with a particle size of 10 μm or larger in the total inorganic particles are calculated as follows.
[0127] Inorganic particles are left by sintering a resin substrate (or resin substrate and adhesive layer if an adhesive layer is present, hereinafter the same) to decompose and remove at least a portion of the resin from the resin substrate. The remaining inorganic particles are then dispersed in ethanol. The volumetric particle size distribution of the resulting dispersion is determined using a laser diffraction particle size distribution measuring device (e.g., Malvern Mastersizer 2000, Horiba Manufacturing Co., Ltd. LA-920 laser diffraction / scattering particle size distribution measuring device, etc.) via a wet method. Based on the obtained particle size distribution, the proportion (volume %) of inorganic particles with a diameter of 1 μm or larger in the total inorganic particles is determined.
[0128] There are no particular limitations on the method of forming the adhesive layer. For example, methods such as coating the adhesive layer forming composition onto a resin substrate and co-extruding the adhesive layer forming material and the resin substrate forming material can be used to form the adhesive layer.
[0129] In addition, as a method for forming an adhesive layer, there are also methods for coating an adhesive layer forming composition on the surface of a biaxially stretched resin substrate, and methods for coating an adhesive layer forming composition on the surface of a resin substrate stretched along a first direction (e.g., MD: Machine Direction), and then stretching the coating of the adhesive layer forming composition along the surface of the resin substrate in a second direction (e.g., TD: Transverse Direction) orthogonal to the first direction together with the resin substrate.
[0130] (Level 1)
[0131] The first layer contains microcapsules containing color-developing agents.
[0132] First, we will describe in detail the materials that make up the microcapsules.
[0133] Microcapsules typically have a core and a capsule wall for containing the core material (the contained substance, also known as the inclusion component) that forms the core.
[0134] In this invention, the microcapsules contain a color-developing agent as a core material (containing component). Because the color-developing agent is contained within microcapsules, it can remain stable until the microcapsules are pressurized and destroyed.
[0135] Microcapsules have capsule walls containing a core material.
[0136] As materials for the capsule walls of microcapsules, known resins that have been used in applications such as pressure-sensitive copy paper or thermal recording paper as wall materials for microcapsules containing color-developing agents can be cited. Specifically, polyurethane, polyurea, polyurethane urea, melamine-formaldehyde resin, and gelatin can be cited as such resins.
[0137] In view of further improving the effects of the present invention, it is preferable that the capsule wall of the microcapsule contains at least one resin selected from polyurethane urea, polyurethane and polyurea.
[0138] The capsule wall of the microcapsule is preferably substantially composed of resin. "Substantially composed of resin" means that the resin content is 90% by mass or more, preferably 100% by mass, relative to the total mass of the capsule wall. That is, the capsule wall of the microcapsule is preferably composed of resin.
[0139] It should be noted that polyurethane refers to a polymer having multiple urethane bonds, preferably a reaction product formed from raw materials containing polyols and polyisocyanates.
[0140] Furthermore, polyurea refers to a polymer having multiple urea bonds, and is preferably a reaction product formed from raw materials containing polyamines and polyisocyanates. It should be noted that a portion of the polyisocyanate can also be reacted with water to form a polyamine, thus synthesizing polyurea using polyisocyanates instead of polyamines.
[0141] Furthermore, polyurethane urea refers to a polymer containing urethane bonds and urea bonds, and is preferably a reaction product formed from raw materials comprising polyols, polyamines, and polyisocyanates. It should be noted that when a polyol reacts with a polyisocyanate, a portion of the polyisocyanate reacts with water to form a polyamine, sometimes resulting in a polyurethane urea.
[0142] In addition, the melamine-formaldehyde resin is preferably a reaction product formed by the condensation polymerization of melamine and formaldehyde.
[0143] It should be noted that the aforementioned polyisocyanates refer to compounds having two or more isocyanate groups, including aromatic polyisocyanates and aliphatic polyisocyanates. Examples of polyisocyanates include adducts (additions) of polyols such as trimethylolpropane with difunctional polyisocyanates.
[0144] In addition, the aforementioned polyols refer to compounds having two or more hydroxyl groups, such as low molecular weight polyols (e.g., aliphatic polyols, aromatic polyols. It should be noted that "low molecular weight polyols" refers to polyols with a molecular weight of less than 400), polyvinyl alcohol, polyether polyols, polyester polyols, polylactone polyols, castor oil polyols, polyolefin polyols, and hydroxyl-containing amine compounds (e.g., amino alcohols. Examples of amino alcohols include N,N,N',N'-tetra[2-hydroxypropyl]ethylenediamine, an adduct of propylene oxide or ethylene oxide, which is an amino compound such as ethylenediamine).
[0145] In addition, the aforementioned polyamines refer to compounds having two or more amino groups (primary or secondary amino groups), such as aliphatic polyamines like diethylenetriamine, triethylenetetramine, 1,3-propanediamine, and hexamethylenediamine; epoxy adducts of aliphatic polyamines; alicyclic polyamines like piperazine; and heterocyclic diamines like 3,9-diaminopropyl-2,4,8,10-tetraoxaspiro-(5,5)undecane.
[0146] The glass transition temperature of the capsule wall of the microcapsule is not particularly limited, but is preferably 50 to 160°C, and more preferably 80 to 150°C.
[0147] The method for determining the glass transition temperature of the capsule wall is as follows.
[0148] Prepare 50 sheets of material 1cm long × 1cm wide, immerse them all in 10ml of water and let them stand for 24 hours to obtain an aqueous dispersion of microcapsules.
[0149] The obtained aqueous dispersion of microcapsules was centrifuged at 15,000 rpm for 30 minutes to separate and extract the microcapsules. Ethyl acetate was added to the extracted microcapsules, and the mixture was further stirred at 25°C for 24 hours. The resulting solution was then filtered, and the residue was vacuum-dried at 60°C for 48 hours to obtain microcapsules without any internal contents (hereinafter referred to as "test material"). That is, the capsule wall material of the microcapsules used for measuring the glass transition temperature was obtained.
[0150] Next, the thermal decomposition temperature of the obtained test material was determined using a thermogravimetric differential thermal analysis (TG-DTA) apparatus (device name: DTG-60, Shimadzu Corporation). It should be noted that the thermal decomposition temperature is defined as the temperature at which the mass of the test material decreases by 5% relative to its initial mass during thermogravimetric analysis (TGA) in atmospheric atmosphere, achieved by heating the test material from room temperature at a constant heating rate (10°C / min).
[0151] Next, the glass transition temperature of the test material was measured using a differential scanning calorimeter (DSC-60a Plus, Shimadzu Corporation) with a closed pan and a heating rate of 5°C / min within the range of 25°C to (thermal decomposition temperature (°C) - 5°C). The glass transition temperature of the microcapsule wall was used as the value at the second heating cycle.
[0152] The average particle size of the microcapsules is not particularly limited, but is preferably 1 to 80 μm, more preferably 5 to 70 μm, and even more preferably 10 to 50 μm, based on the median particle size (D50) on a volume basis.
[0153] The median particle size of microcapsules on a volume basis can be controlled by adjusting the manufacturing conditions of the microcapsules.
[0154] Here, the median particle size of a microcapsule, based on volume, refers to the diameter at which the total volume of particles on the larger and smaller diameter sides equals the total volume of the microcapsule when the microcapsule is divided into two parts with a threshold of 50% volume. That is, the median particle size is equivalent to the so-called D50.
[0155] The value is calculated by taking a 1000x optical microscope image of the surface of the first layer of the first sheet containing the first layer of microcapsules and measuring the size of all microcapsules within a range of 500μm × 500μm.
[0156] The number-average wall thickness (number-average wall thickness of the capsule wall) of the microcapsules is not particularly limited, but is preferably 0.01 μm or more and 2 μm or less, more preferably more than 0.02 μm and less than 2 μm, and even more preferably 0.05 μm or more and 1.5 μm or less.
[0157] It should be noted that the wall thickness of a microcapsule refers to the thickness (μm) of the capsule wall of the microcapsule particles forming the microcapsule. The number-average wall thickness is the average value obtained by averaging the individual capsule wall thickness (μm) of five microcapsules obtained using a scanning electron microscope (SEM). More specifically, a cross-sectional section of a first sheet containing a first layer of microcapsules is prepared. The cross-section is observed at 200x magnification using an SEM. Five microcapsules with a major axis ranging from (average microcapsule diameter) × 0.9 to (average microcapsule diameter) × 1.1 are selected. Then, the cross-section of each selected microcapsule is observed at 15000x magnification, and the capsule wall thickness is determined and averaged. It should be noted that the major axis refers to the longest diameter observed when the microcapsule is viewed.
[0158] The ratio (δ / Dm) of the number-average wall thickness δ of the microcapsules to the average particle size Dm of the microcapsules is not particularly limited, and is often greater than 0.001. However, from the perspective of better performance of the present invention, it is preferable to satisfy the relationship of equation (1).
[0159] Equation (1) 0.100>δ / Dm>0.001
[0160] That is, the ratio (δ / Dm) is preferably greater than 0.001 and less than 0.100. If the relationship of equation (1) is satisfied, it can be set to a range in which the color intensity gradation can be easily identified based on pressure.
[0161] [Coloring agent]
[0162] The microcapsules contain a color-developing agent.
[0163] A chromogenic agent is a compound that develops color from a colorless state through contact with a chromogenic agent (described later). As a chromogenic agent, an electron-donating pigment precursor (a precursor of the chromogenic pigment) is preferred. That is, an electron-donating colorless dye is preferred as a chromogenic agent.
[0164] Color-developing agents are those known for their use in pressure-sensitive copy paper or thermal recording paper. Examples of color-developing agents include triphenylmethane phthalide compounds, fluorane compounds, phenothiazine compounds, indole phthalide compounds, azaindole phthalide compounds, leucochromauramine compounds, rhodamine lactam compounds, triphenylmethane compounds, diphenylmethane compounds, triazine compounds, spiropyran compounds, and fluorene compounds.
[0165] Examples of the aforementioned compounds include those described in Japanese Patent Application Publication No. 5-257272, those described in paragraphs 0030 to 0033 of International Publication No. 2009 / 8248, 3',6'-bis(diethylamino)-2-(4-nitrophenyl)spirocyclic [isoindol-1,9'-xanthon]-3-one, 6'-(diethylamino)-1',3'-dimethylfluorane, and 3,3-bis(2-methyl-1-octyl-3-indolyl)phthalide.
[0166] There is no particular limitation on the molecular weight of the colorant, but it is preferably 300 or higher. There is no particular upper limit, but it is preferably 1000 or lower.
[0167] [Other ingredients]
[0168] Microcapsules may also contain other ingredients besides the colorants mentioned above.
[0169] For example, microcapsules preferably contain a solvent.
[0170] There are no particular restrictions on solvents. Examples include alkylnaphthalene compounds such as diisopropylnaphthalene, diarylalkane compounds such as 1-phenyl-1-dimethylethane, alkylbiphenyl compounds such as isopropyl biphenyl, triarylmethane compounds, alkylbenzene compounds, benzylnaphthalene compounds, diarylalkylene compounds, and arylindenhydrides; aliphatic hydrocarbons such as dibutyl phthalate and isoparaffins; natural vegetable and animal oils such as soybean oil, corn oil, cottonseed oil, rapeseed oil, olive oil, coconut oil, castor oil, and fish oil; and high-boiling fractions of natural substances such as mineral oil.
[0171] When the microcapsule contains a solvent, the mass ratio of solvent to colorant (mass of solvent / mass of colorant) is preferably in the range of 98 / 2 to 30 / 70 from the viewpoint of color development, and more preferably in the range of 97 / 3 to 40 / 60.
[0172] In addition to the above-mentioned ingredients, microcapsules may also contain one or more additives such as ultraviolet absorbers, light stabilizers, antioxidants, waxes, and odor inhibitors, as needed.
[0173] [Methods for manufacturing microcapsules]
[0174] There are no particular limitations on the manufacturing method of microcapsules; for example, known methods such as interfacial polymerization, internal polymerization, phase separation, external polymerization, and coacervation can be cited. Among these, interfacial polymerization is preferred.
[0175] The following describes the interfacial polymerization method using a method for manufacturing microcapsules with polyurea or polyurethane urea as an example.
[0176] As an interfacial polymerization method, an interfacial polymerization method comprising the following steps is preferred: a step of preparing an emulsion by dispersing an oil phase containing a colorant, a solvent with a boiling point of 100°C or higher, and a capsule wall material (e.g., a raw material containing a polyisocyanate and at least one selected from polyols and polyamines. It should be noted that when a polyisocyanate is reacted with water to produce a polyamine in the system, polyols and polyamines may not be used.) in an aqueous phase containing an emulsifier (emulsification step); and a step of polymerizing the capsule wall material at the interface between the oil phase and the aqueous phase to form a capsule wall, thereby forming microcapsules containing the colorant (encapsulation step).
[0177] It should be noted that the mass ratio of the total amount of polyols and polyamines to the amount of polyisocyanate in the above raw materials (total amount of polyols and polyamines / amount of polyisocyanate) is not particularly limited, but is preferably 0.1 / 99.9 to 30 / 70, and more preferably 1 / 99 to 25 / 75.
[0178] In addition, there are no particular restrictions on the types of emulsifiers used in the above emulsification process; for example, dispersants and surfactants can be cited.
[0179] Examples of dispersants include polyvinyl alcohol.
[0180] In addition to the microcapsules mentioned above, the first layer may also contain other components (such as binders and surfactants).
[0181] In addition, the mass per unit area of the first layer (g / m²) 2 (No particular limitation is specified, but considering the superior effects of the present invention, a concentration of 0.5 to 30 g / m is preferred.) 2 .
[0182] (Method for forming the first layer)
[0183] There are no particular restrictions on the method of forming the first layer mentioned above.
[0184] For example, a method can be described by coating a first layer forming composition containing microcapsules onto a resin substrate (or an adhesive layer) and subjecting the resulting coating to a heat treatment at a specified temperature or higher.
[0185] It should be noted that, in addition to the above, another method can be given, which involves separately preparing microcapsules and coating a first layer forming composition containing microcapsules onto a resin substrate (or an adhesive layer).
[0186] The following details the methods of heating above a specified temperature.
[0187] The composition for forming the first layer preferably contains at least microcapsules and a solvent. It should be noted that the microcapsule dispersion obtained by the above-described interfacial polymerization method can also be used as the composition for forming the first layer.
[0188] The composition for forming the first layer may contain other components that may be included in the first layer as described above.
[0189] There are no particular limitations on the method of coating the first layer of the composition. Examples of coating machines used for coating include air knife coating machines, bar coating machines, rod coating machines, curtain coating machines, gravure coating machines, extrusion coating machines, die coating machines, sliding bead coating machines, and doctor blade coating machines.
[0190] After the first layer forming composition is applied to a resin substrate (or an adhesive layer), the resulting coating film is subjected to a heat treatment at a specified temperature or higher.
[0191] The optimal temperature for heat treatment is selected based on the material of the capsule wall of the microcapsules used. From the perspective of maximizing the effectiveness of the present invention, a temperature of 60°C or higher is preferred, and 70°C or higher is more preferable. There is no particular upper limit, and temperatures below 180°C are common. From the perspective of achieving superior color concentration, temperatures below 140°C are preferred, and 120°C or lower is more preferable.
[0192] There is no particular limitation on the heating time, but from the perspective of improving the effect of the present invention and productivity, it is preferred to be 1.0 to 20 minutes, and more preferably 3.0 to 10 minutes.
[0193] It should be noted that the method of forming the first layer on the resin substrate (or the adhesive layer) has been described above, but it is not limited to the above method. For example, the first layer can also be formed on the temporary support and then transferred to the resin substrate.
[0194] As a temporary support, there are no particular restrictions as long as it is a detachable support.
[0195] (spacer)
[0196] The material of the spacer is not particularly limited, but a foamed rubber or a foamed elastomer is preferred. Examples of foamed rubber include those selected from natural rubber, isoprene rubber, styrene rubber, nitrile rubber, butadiene rubber, chloroprene rubber, and urethane rubber. Examples of foamed elastomers include those selected from polyethylene, polypropylene, polystyrene, polyvinyl chloride, and polyvinyl acetate.
[0197] The thickness of the spacer is not particularly limited, but it is preferably thicker than the first layer.
[0198] The thickness of the spacer is often 1 to 10 mm. However, considering the superior effect of the present invention, it is preferred to be 1 to 5 mm, and more preferably 2.5 to 5 mm.
[0199] The static friction coefficient of the spacer is not particularly limited, but from the perspective of better performance of the present invention, it is preferably 0.1 to 1.0.
[0200] The coefficient of dynamic friction of the spacer is not particularly limited, but from the perspective of better performance of the present invention, it is preferably 0.1 to 1.0.
[0201] There are no particular limitations on the method of placing spacers on the first sheet; examples include using double-sided tape and using adhesives or bonding agents.
[0202] There are no particular limitations on the arithmetic mean roughness Ra of the first sheet, and it is often greater than 0.1 μm. However, from the perspective of superior color concentration, 2.5 to 7.0 μm is preferred. It should be noted that the arithmetic mean roughness Ra of the first sheet refers to the arithmetic mean roughness Ra of the surface of the first sheet on the side opposite to the second sheet (the contact side) when using the sheet group for pressure testing. When the first layer is located on the outermost surface of the first sheet on the side opposite to the second sheet, the above-mentioned arithmetic mean roughness Ra is equivalent to the arithmetic mean roughness Ra of the surface of the first layer opposite to the resin substrate side.
[0203] It should be noted that the arithmetic mean roughness Ra (arithmetic mean roughness Ra of the first sheet and arithmetic mean roughness Ra of the second sheet described later) in this specification refers to the arithmetic mean roughness Ra specified in JIS B 0681-6:2014. It should also be noted that the measuring apparatus used is a scanning white interferometer utilizing optical interference (specifically, a NewView 5020 manufactured by Zygo Corporation; objective lens × 50x; intermediate lens × 0.5x). The measurement mode for measuring the arithmetic mean roughness Ra of the first sheet using the above-mentioned scanning white interferometer is Stich mode, and the measurement mode for measuring the arithmetic mean roughness Ra of the second sheet is Micro mode.
[0204] It should be noted that, in Figures 1-3 In the assembly 10 shown, the insertion part 20 of the flange member 14 is inserted into the hollow part of the core 12 to fix the two together, but the method of fixing is not limited to this method.
[0205] For example, the outer peripheral surface of the end of the core may have a protrusion, and the flange member may have a recess for the end of the core to be inserted into. The end of the core is inserted into the recess, and the protrusion of the core contacts the flange member, thereby fixing the core to the flange member.
[0206] Alternatively, other fixing methods besides using protrusions can be employed. For example, the core and flange member can be bonded together with adhesive. Alternatively, the core and flange member can be threaded together.
[0207] The assembly of the present invention can also be contained within a packaging body. It can be a bag or a container comprising a container body with an opening and a lid that plugs the opening.
[0208] There are no particular limitations on the materials that make up the packaging body; examples include resins, and more specifically, polyolefin resins, polyethylene resins, and polypropylene resins.
[0209] There are no particular limitations on the color of the packaging; transparent, brown, and black are examples. However, from the viewpoint of lightfastness, brown or black is preferred, and black is even more preferred.
[0210] <Second Sheet>
[0211] The assembly of the present invention can also be combined with a second sheet having a second layer containing a color developer to form a sheet assembly for pressure measurement.
[0212] The second sheet can be treated as an assembly. That is, the sheet assembly for pressure measurement of the present invention can also be composed of a first assembly and a second assembly. The first assembly has a core, a pair of flange members fixed to both ends of the core, and a first sheet having a first layer containing microcapsules containing a color-developing agent wound around the core. The second assembly has a core, a pair of flange members fixed to both ends of the core, and a second sheet having a second layer containing a color-developing agent wound around the core.
[0213] When using the pressure testing sheet assembly, the first sheet and the second sheet are laminated with the first layer of the first sheet facing each other and the second layer of the second sheet facing each other. By applying pressure to the resulting laminate, microcapsules rupture in the pressurized area, releasing the color-developing agent contained within the microcapsules, which then reacts with the color-developing agent in the second layer. As a result, color development occurs in the pressurized area.
[0214] The second sheet has a second layer containing a color developer. Preferably, the second sheet includes a support and a second layer disposed on the support.
[0215] The following is a detailed description of each component.
[0216] (Support structure)
[0217] The support is a component used to support the second layer. It should be noted that the second sheet may not need a support if it can be processed using the second layer itself.
[0218] The support can be any shape, either sheet-like or plate-like.
[0219] Examples of supports include resin substrates and synthetic paper, with resin substrates being preferred. Examples of resin substrates include those incorporated in the first sheet described above.
[0220] Furthermore, as a support, the laminate of the resin substrate and the adhesive layer described in the first sheet above can also be cited. The preferred configuration of the resin substrate and the adhesive layer is as described above.
[0221] The support in the first sheet can be the same as or different from the support in the second sheet.
[0222] From the perspective of easily visually identifying the color development state after pressure measurement through the support, the support in the second sheet is preferably transparent, and the haze of the support is preferably 0 to 20%, more preferably 0 to 10%.
[0223] (Level 2)
[0224] The second layer contains the color developer.
[0225] A color developer is a compound that does not itself have color-developing properties, but has the property of causing the color-developing agent to develop color through contact with it. Compounds with electron accepting properties are preferred as color developers.
[0226] Inorganic and organic compounds can be used as color developers, with those described in paragraphs 0055-0056 of International Publication No. 2009 / 008248 being preferred. From the perspective of superior color concentration and image quality after color development, acidic clay, activated clay, or metal salts of aromatic carboxylic acids are preferred.
[0227] The content of the color developer in the second layer is not particularly limited, but from the perspective of better color concentration, it is preferably 20 to 95% by mass relative to the total mass of the second layer, and more preferably 30 to 90% by mass.
[0228] The content of the color developer in the second layer is not particularly limited, but is preferably 0.1 to 30 g / m.2 When the colorimetric reagent is an inorganic compound, the preferred content of the colorimetric reagent is 3–20 g / m³. 2 More preferably 5-15 g / m 2 When the color developer is an organic compound, the preferred content of the color developer is 0.1–5 g / m³. 2 More preferably, it is 0.2–3 g / m 2 .
[0229] The second layer may contain other components besides the color developer mentioned above.
[0230] Other components include, for example, polymeric binders, pigments, fluorescent whitening agents, defoamers, penetrants, UV absorbers, surfactants, and preservatives.
[0231] Examples of polymeric binders include styrene-butadiene copolymers, polyvinyl acetate, polyacrylates, polyvinyl alcohol, polyacrylic acid, maleic anhydride-styrene copolymers, olefin resins, modified acrylate copolymers, starch, casein, gum arabic, gelatin, carboxymethyl cellulose or its salts, and methyl cellulose, among other synthetic and natural polymers.
[0232] Examples of pigments include heavy calcium carbonate, light calcium carbonate, talc, and titanium dioxide.
[0233] The thickness of the second layer is not particularly limited, but from the perspective of better performance of the present invention, it is preferably 1 to 50 μm, and more preferably 2 to 30 μm.
[0234] In addition, the mass per unit area of the second layer (g / m²) 2 (No particular limitation is specified, but considering the superior effects of the present invention, a concentration of 0.5 to 30 g / m is preferred.) 2 .
[0235] (Method for forming the second layer)
[0236] There are no particular restrictions on the method of forming the second layer mentioned above.
[0237] For example, a method can be described by coating a second layer forming composition containing a color developer onto a support and drying the resulting coating as needed.
[0238] The composition for forming the second layer can also be a dispersion of a color developer in water or the like. When the color developer is an inorganic compound, the dispersion can be prepared by mechanically dispersing the inorganic compound in water. Alternatively, when the color developer is an organic compound, it can be prepared by mechanically dispersing the organic compound in water or dissolving it in an organic solvent.
[0239] The composition for forming the second layer may contain other components that may be included in the second layer as described above.
[0240] There are no particular limitations on the method of applying the composition for forming the second layer; for example, a method using a coating machine for applying the composition for forming the first layer described above can be cited.
[0241] After the second layer forming composition is applied to the support, the coating can be dried as needed. One example of a drying process is heat treatment.
[0242] It should be noted that the method of forming a second layer on the support has been described above, but it is not limited to the above method. For example, after forming a second layer on the temporary support, the temporary support can be peeled off to form a second sheet composed of the second layer.
[0243] As a temporary support, there are no particular restrictions as long as it is a detachable support.
[0244] (Other components)
[0245] The second sheet may also have the aforementioned support and other components besides the second layer.
[0246] For example, the second sheet may have an adhesive layer between the support and the second layer to improve the adhesion between the two.
[0247] Examples of adhesive layer types include those that the first sheet described above can have.
[0248] As described above, the first sheet and the second sheet are used to obtain a laminate by laminating the first sheet and the second sheet with the first layer of the first sheet facing each other, and then pressurizing the laminate.
[0249] That is, the first sheet is equivalent to the sheet used to measure pressure together with the second sheet mentioned above.
[0250] From the perspective of achieving superior color intensity, the arithmetic mean roughness Ra of the second sheet is preferably 1.2 μm or less. It should be noted that the arithmetic mean roughness Ra of the second sheet refers to the arithmetic mean roughness Ra of the surface of the second sheet on the side opposite to the first sheet (the contact side) when using the pressure testing sheet assembly. When the second layer is located on the outermost surface of the second sheet on the side opposite to the first sheet, the aforementioned arithmetic mean roughness Ra corresponds to the arithmetic mean roughness Ra of the surface of the second layer on the side opposite to the support body.
[0251] Example
[0252] The present invention will now be described in more detail based on embodiments. The materials, amounts, proportions, processing contents, and processing steps shown in the following embodiments may be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the invention should not be interpreted as limited by the embodiments shown below. It should be noted that, unless otherwise specified, "parts" and "%" are based on mass.
[0253] <Example 1>
[0254] After biaxial stretching, a strip of polyethylene terephthalate (PET) film (450 mm wide) with a thickness of 75 μm was prepared, with both sides subjected to corona discharge treatment. Next, the adhesive layer forming composition A (described later) was coated onto one surface of the obtained PET film using a bar coater and dried to form an adhesive layer A with a thickness of 0.45 μm.
[0255] The composition of composition A for forming the sealing layer is as follows.
[0256] It should be noted that when the total mass of the composition is set to 100 parts by mass, the mass of each dispersion is expressed as "parts by mass".
[0257] -Composition A for forming a tight layer--
[0258] • Styrene / butadiene copolymer latex (styrene:butadiene = 67:30, product name: LX-407C5, manufactured by ZEON Corporation, Japan, solid content 40% by weight) 14.1 parts by weight
[0259] 2,4-Dichloro-6-hydroxytriazine (8% by weight of solids) 2.5 parts by weight
[0260] • Polystyrene particles (product name: UFN1008, manufactured by ZEON Corporation, Japan, average particle size: 2μm, solid content 20% by mass) 0.04 parts by mass
[0261] · Distilled water 83.4 parts by weight
[0262] Next, the adhesive layer forming composition B, consisting of the following components, is applied onto the adhesive layer A using a bar coater and dried to form an adhesive layer B with a thickness of 0.1 μm, thus obtaining the support 1.
[0263] -Composition B for forming a tight layer--
[0264] 10 parts of a 10.4% aqueous solution of gelatin (761 gelatin, manufactured by Nitta Gelatin Co., Ltd., 100% solids).
[0265] 0.04 parts of a 3.5% methanol solution of 1,2-benzothiazolin-3-one
[0266] • 0.67 parts of a 3% aqueous solution of hydroxypropyl methylcellulose (METOLOSE TC5R, manufactured by Shin-Etsu Chemical Co., Ltd., 100% solids)
[0267] • 0.7 parts of a 1% aqueous solution of sodium hydroxide (NAROACTY CL-95: manufactured by Sanyo Chemical Industry Co., Ltd., 1% solid content)
[0268] • Antimony-doped tin oxide dispersion (TDL-S: manufactured by Mitsubishi Materials Co., Ltd., 17% solids, antistatic inorganic particles) 4.9 parts
[0269] · Distilled water 83.7 parts
[0270] 3,3-bis(2-methyl-1-octyl-3-indolyl)phthalide (18 parts by mass), used as a color-developing agent, is dissolved in diarylethane (70 parts by mass) to obtain solution A. Separately, 0.4 parts by mass of the ethylenediamine butyroxene adduct dissolved in methyl ethyl ketone (1 part by mass) is added to solution A while it is being stirred to obtain solution B. Furthermore, 2 parts by mass of the toluene diisocyanate trimethylolpropane adduct dissolved in methyl ethyl ketone (1 part by mass) is added to solution B while it is being stirred to obtain solution C.
[0271] Next, solution C was added to a solution containing polyvinyl alcohol (6 parts by mass) dissolved in water (150 parts by mass) for emulsification and dispersion. Water (300 parts by mass) was added to the emulsion, and the mixture was heated to 70°C while stirring for 1 hour, then cooled to prepare a microcapsule solution containing microcapsules with a color-developing agent. The average particle size of the obtained microcapsules was 20 μm. The prepared microcapsule solution was used as microcapsule solution (A) containing the color-developing agent.
[0272] Water (75 parts by mass), sodium polyacrylate (5 parts by mass), and calcium carbonate (100 parts by mass) were mixed and dispersed using a sand mill. Then, SBR latex (equivalent to 15 parts by mass of solids), 1% aqueous solution of carboxymethyl cellulose (15 parts by mass), and 25% aqueous solution of sodium dodecylbenzenesulfonate (1 part by mass) were added and mixed. Water was then added to adjust the solids concentration to 41.5% by mass, thus preparing a composition for ear protection.
[0273] Next, on the sealing layer B of the support 1, protective ear layers are formed at both ends of the support 1 in the width direction, and a first layer is formed between the protective ear layers. First, the microcapsule liquid (A) containing the colorant is coated on the surface of the sealing layer B of the support 1 with a width of 450 mm. Then, the protective ear layer forming composition is coated in a manner that contacts both ends in the width direction, and then dried to obtain a sheet. In the obtained sheet, the width of the first layer is 400 mm, and the width of the protective ear layer is 25 mm on one side (50 mm on both sides).
[0274] Next, by removing the protective ear layers at both ends of the obtained sheet in the width direction, the central portion of the sheet is cut into strips 360mm wide using a processing machine, resulting in a first strip having a support 1 and a first layer disposed on the support 1. Double-sided adhesive tape is then applied to both ends of the obtained first strip in the width direction, and cushioning material (spacers) is attached to create the first strip. Figure 5 and Figure 6 The first sheet, as shown, has spacers arranged throughout its length.
[0275] Next, prepare the hollow cylindrical core and the flange member, which will be described later. It should be noted that the flange member has a base plate and a cylindrical insertion portion disposed on the base plate, and a protrusion is disposed on the surface of the insertion portion (see reference). Figure 2 and Figure 3 Insert the insert of the flange member into the hollow part of the core, fix the flange members at both ends of the core, and make a core with flange members.
[0276] Next, a core containing spacers is wound around a flanged core to create a roll with a cross-sectional diameter (outer diameter of the roll of the first sheet) of 170 mm at both ends. Figure 1 As shown in the figure, assembly 1.
[0277] -spacer-
[0278] Material: Neoprene foam rubber (manufactured by Tokiwa Rubber Co., Ltd.), width: 15mm, thickness: 5mm, static friction coefficient: 0.63, dynamic friction coefficient: 0.62
[0279] -Double-sided tape-
[0280] Japanese paper + acrylic adhesive (manufactured by Sekisui Chemicals Co., Ltd., Double Tack Tape #595), width: 10mm
[0281] -Coil Core-
[0282] Paper (resin impregnated), length: 390mm, inner diameter of hollow section: 76mm
[0283] -Flange member (refer to) Figure 2 )-
[0284] Material: Polypropylene (PP); Substrate shape: Octagonal; Substrate size: 210mm; Diameter of circumscribed circle (the diameter of the circumscribed circle of the flange member when viewed from the normal direction of the substrate, circumscribed with the area formed by the insertion part and the protrusion): 77.5mm; Number of protrusions: 8 evenly spaced; Protrusion height: 1.3mm
[0285] <Examples 2-15, Comparative Example 1>
[0286] Except for the changes to the various conditions shown in Table 1 below, assemblies 2 to 15 of Examples 2 to 15 and assembly C1 of Comparative Example 1 were prepared according to the same steps as in Example 1.
[0287] It should be noted that the supports 2 to 14 listed in the table are manufactured using the following methods.
[0288] (Construction of Support 2)
[0289] Composition C for forming an adhesive layer is prepared in the same manner as composition A for forming an adhesive layer, except that the styrene / butadiene copolymer latex is replaced with a styrene-acrylic copolymer (AS-563A, manufactured by Daicel Fine Chem Co., Ltd., solid content 27.5% by mass).
[0290] Except for changing the adhesive layer forming composition A to the adhesive layer forming composition C and changing the thickness, the same operation as for the support 1 is performed to obtain the support 2.
[0291] (Preparation of support structures 3, 5-14)
[0292] Except for the changes to the various conditions shown in Table 1 described later, the same procedure as for support 1 is followed to obtain supports 3, 5 to 14.
[0293] (Preparation of support 4)
[0294] Composition C for forming an adhesive layer is coated on both sides of a 75 μm thick strip of polyethylene terephthalate (PET) film uniaxially stretched along its length and then dried. Next, it is stretched along its width, heat-set, and heat-relaxed to obtain support 4.
[0295] <Production of the Second Sheet>
[0296] Activated clay (BYK-chemie, FURACOLOR SR) (100 parts by weight), sodium hexametaphosphate (Nippon Chemical Industry, sodium hexametaphosphate) (0.5 parts by weight), 10% sodium hydroxide aqueous solution (15 parts by weight), and water (240 parts by weight) were added to the resulting dispersion. This was then mixed with olefin resin (Arakawa Chemical Industry, Polymaron 482) (30 parts by weight), modified acrylate copolymer (Nippon ZEON, Nippon LX814) (35 parts by weight), 1% aqueous solution of sodium carboxymethyl cellulose (Daiichi Kogyo Pharmaceutical, Cellogen EP) (80 parts by weight), 15% aqueous solution of alkylbenzene sulfonate Na (Daiichi Kogyo Pharmaceutical, NEOGEN T) (18 parts by weight), and polyoxyethylene polyoxypropylene lauryl ether (Daiichi Kogyo Pharmaceutical, NOIGEN). A composition for forming a second layer containing clay material was obtained by mixing 20 parts by mass of a 1% aqueous solution of LP-70 and 20 parts by mass of sodium-bis(3,3,4,4,5,5,6,6,6-nonafluorohexyl)-2-sulfinatooxysuccinate (Fujifilm, W-AHE).
[0297] The above-mentioned composition for forming the second layer is applied at a solid content of 7 g / m². 2 The coating is applied to the support 1 in a specific manner. Next, the resulting coating is dried to form a second layer, resulting in a second sheet. It should be noted that the haze of the support 1 is less than 10%.
[0298] <Measurement>
[0299] (Stiffness)
[0300] Test pieces with a length (longitudinal) of 200 mm and a width (transverse) of 15 mm were cut from the first sheet prepared in each embodiment and comparative example. The stiffness of the first sheet in the length and width directions was measured using a LOOP STIFF NESS TESTER (manufactured by Toyo Seiki Co., Ltd.). The measurement conditions were set as follows: clamp spacing distance 100 mm, ring length 85 mm, and compression speed 3.3 mm / s. The above measurements were performed on two test pieces. The average length direction stiffness obtained from the two test pieces was taken as the length direction stiffness of the first sheet, and the average width direction stiffness obtained from the two test pieces was taken as the width direction stiffness of the first sheet. It should be noted that when measuring the length direction stiffness of the first sheet, a test piece cut with the length direction of the test piece along the length direction of the first sheet was used; similarly, when measuring the width direction stiffness of the first sheet, a test piece cut with the length direction of the test piece along the width direction of the first sheet was used.
[0301] <Evaluation>
[0302] (Drop test)
[0303] Based on the flow condition level I of JIS Z0202, each assembly was subjected to a 1-corner, 3-edge, 6-face drop test and evaluated according to the following criteria. The results are shown in Table 1.
[0304] A: No signs of damage to the microcapsules were observed.
[0305] B: Slight signs of microcapsule damage were observed (to a usable level).
[0306] C: Traces of damage to multiple microcapsules were observed.
[0307] (Color development granularity)
[0308] The first sheet contained in each assembly and the second sheet, cut to a size of 5cm x 5cm, were overlapped with the surface of the first layer of the first sheet facing the surface of the second layer of the second sheet. The two overlapping sheets were placed on a table between two smooth glass plates, and weights were placed on the glass plates to apply pressure of 0.2MPa to induce color development. The color development surface of the second sheet was then visually observed from the support (PET sheet) side through the support, and evaluated according to the evaluation criteria below. It should be noted that the capsule of the sample in Comparative Example 1 was destroyed in the drop test, and therefore was not evaluated. The evaluation results are shown in Table 1.
[0309] A: The graininess of the hair color is very small.
[0310] B: The color has a slightly grainy texture, but it's not a problem in practical use.
[0311] C: The grainy texture of the colored surface is noticeably larger.
[0312] Table 1
[0313]
[0314] As shown in Table 1, the desired effect was obtained when the assembly of the present invention was used.
[0315] In comparison with other embodiments, it was confirmed that when the thickness of the spacer is 2.5 μm or more, better results can be obtained.
[0316] Furthermore, based on comparisons of Examples 8, 10, and 15 with other examples, it was confirmed that when the stiffness of the first sheet in the width direction (transverse direction) is 165 mN or more, even better results can be obtained.
[0317] Furthermore, based on a comparison of Embodiments 10 and 15 with other embodiments, it was confirmed that when the stiffness in the width direction / the stiffness in the length direction is 1.00 or higher, a better effect can be obtained.
[0318] Furthermore, based on a comparison of Example 12 with other examples, it was confirmed that when the thickness of the adhesive layer is less than 2.0 μm, a more superior color graininess can be obtained.
[0319] Furthermore, based on a comparison of Example 14 with other examples, it was confirmed that with the presence of a sealing layer, superior results and excellent color particle texture can be obtained.
[0320] <Example 16>
[0321] 15 parts by mass of synthetic isoparaffin (Idemitsu Kosan Co., Ltd., IP Solvent 1620) and 0.4 parts by mass of N,N,N',N'-tetra(2-hydroxypropyl)ethylenediamine (Adeka Co., Ltd., ADEKA PolyetherEDP-300) dissolved in ethyl acetate (3 parts by mass) were added to 78 parts by mass of 1-phenyl-1-dimethylethane (Nippon Oil Co., Ltd., Hisol SAS296) under stirring to obtain solution D.
[0322] In addition, 3 parts by mass of the trimethylolpropane adduct of toluene diisocyanate (DIC Corporation, Burnock D-750) dissolved in ethyl acetate (7 parts by mass) were added to solution D while it was being stirred to obtain solution E.
[0323] Then, polyvinyl alcohol (PVA-205, Kuraray Co., Ltd.) (69 parts by mass) was dissolved in water (140 parts by mass), and solution E was added to the resulting solution for emulsification and dispersion. Water (340 parts by mass) was added to the emulsion, and the mixture was heated to 70°C while stirring for 1 hour, followed by cooling. Water was further added to adjust the concentration, resulting in a microcapsule solution (B) without colorant and containing a solid content of 19.6%.
[0324] The microcapsule solution (A) containing a color-developing agent (18 parts by mass), the microcapsule solution (B) without a color-developing agent (2 parts by mass), water (63 parts by mass), a 10% aqueous solution (1.8 parts by mass) of carboxymethyl cellulose Na (Daiichi Kogyo Pharmaceutical Co., Ltd., Cellogen 5A), a 1% aqueous solution (30 parts by mass) of carboxymethyl cellulose Na (Daiichi Kogyo Pharmaceutical Co., Ltd., Cellogen EP), a 15% aqueous solution (0.3 parts by mass) of sodium alkylbenzene sulfonate (Daiichi Kogyo Pharmaceutical Co., Ltd., NEOGEN T), and a 1% aqueous solution (0.8 parts by mass) of NOIGEN LP70 (Daiichi Kogyo Pharmaceutical Co., Ltd.) were mixed and stirred for 2 hours to obtain a specific composition.
[0325] The assembly 16 was fabricated using the specific composition described above instead of the microcapsule liquid containing the colorant (A), and the PET film used was changed. Otherwise, the assembly 16 was fabricated following the same steps as in Example 1 described above.
[0326] <Examples 17-22, Comparative Example 2>
[0327] Except for the changes shown in Table 2 below, assemblies 17-22 of Examples 17-22 and assembly C2 of Comparative Example 2 were made following the same steps as in Example 16.
[0328] The above measurements and evaluations were performed using assemblies 16–22 and assembly C2 obtained above. The results are summarized in Table 2.
[0329] It should be noted that in the evaluation of colorimetric particle size in Examples 16-22, the pressure was changed to 0.05 MPa for evaluation. The capsule of the sample in Comparative Example 2 was destroyed in the drop test, therefore the colorimetric particle size was not evaluated.
[0330] Table 2
[0331]
[0332] As shown in Table 2, the desired effects can be obtained when using the assembly of the present invention.
[0333] Furthermore, based on the comparison of Examples 16 to 22, it was confirmed that when the stiffness in the width direction is 175mN or more, even better results can be obtained.
[0334] Furthermore, based on a comparison of Example 22 with other examples, it was confirmed that with the presence of a sealing layer, superior results and excellent color particle texture can be obtained.
[0335] Explanation of reference numerals in the attached figures
[0336] 10 Assemblies
[0337] 12 cores
[0338] 14 Flange components
[0339] 16. First roll of sheet material
[0340] 18 substrate
[0341] 20 Insertion section
[0342] 22. Protrusion
[0343] 24 Sheet 1
[0344] 26 Resin substrate
[0345] 28. Sealing layer
[0346] 30 First Floor
[0347] 32 spacers
[0348] 34 Microcapsules
Claims
1. An assembly having: core; and A roll of the first sheet is formed by winding a long strip of the first sheet around the core. The first sheet has a strip-shaped resin substrate and a first layer disposed on the resin substrate, comprising microcapsules containing a color-developing agent. The stiffness of the first sheet in the width direction is above 153mN and below 206mN. The first sheet also has an adhesive layer between the resin substrate and the first layer. The sealing layer is a resin layer containing resin. The method for determining the width direction stiffness of the first sheet is as follows: A test piece with a length of 200 mm and a width of 15 mm was cut from the first sheet. The width stiffness of the cut test piece was measured using a LOOP STIFFNESS TESTER manufactured by Toyo Seiki Co., Ltd. The measurement conditions were set as follows: clamp spacing distance of 100 mm, ring length of 85 mm, and compression speed of 3.3 mm / s. Two test pieces were measured, and the average value of the width stiffness obtained from the two test pieces was taken as the width stiffness of the first sheet. It should be noted that when measuring the width stiffness of the first sheet, a test piece cut with the length of the test piece along the width direction of the first sheet was used.
2. The assembly according to claim 1, wherein, The stiffness of the first sheet in the width direction is greater than the stiffness of the first sheet in the length direction.
3. The assembly according to claim 2, wherein, The stiffness of the first sheet in the longitudinal direction is less than 180mN.
4. The assembly according to any one of claims 1 to 3, wherein, The stiffness of the first sheet in the width direction is 165mN or more.
5. The assembly according to any one of claims 1 to 3, further comprising a pair of spacers disposed between the first sheets of the roll of the first sheet and disposed separately in the width direction of the first sheet.
6. The assembly according to claim 5, wherein, The thickness of the spacer is 1mm to 5mm.
7. The assembly according to claim 1, wherein, The sealing layer comprises a resin having repeating units derived from styrene or its derivatives.
8. The assembly according to claim 1, wherein, The thickness of the sealing layer is 0.01 μm to 2.0 μm.
9. The assembly according to any one of claims 1 to 3, further comprising a pair of flange members fixed to both ends of the core.
10. A sheet assembly for pressure measurement, comprising: The assembly according to any one of claims 1 to 9; and The second sheet has a second layer containing a color developer.
11. A sheet assembly for pressure measurement, comprising: A first sheet having an elongated resin substrate and a first layer disposed on the resin substrate, the first layer comprising microcapsules containing a color-developing agent; and The second sheet has a second layer containing a color developer. The stiffness of the first sheet in the width direction is above 153mN and below 206mN. The first sheet also has an adhesive layer between the resin substrate and the first layer. The sealing layer is a resin layer containing resin. The method for determining the width direction stiffness of the first sheet is as follows: A test piece with a length of 200 mm and a width of 15 mm was cut from the first sheet. The width stiffness of the cut test piece was measured using a LOOP STIFFNESS TESTER manufactured by Toyo Seiki Co., Ltd. The measurement conditions were set as follows: clamp spacing distance of 100 mm, ring length of 85 mm, and compression speed of 3.3 mm / s. Two test pieces were measured, and the average value of the width stiffness obtained from the two test pieces was taken as the width stiffness of the first sheet. It should be noted that when measuring the width stiffness of the first sheet, a test piece cut with the length of the test piece along the width direction of the first sheet was used.
12. A sheet having an elongated resin substrate and a first layer disposed on the resin substrate, the first layer comprising microcapsules containing a color-developing agent. The sheet material has a width direction stiffness of 153 mN or more and 206 mN or less. The sheet also has an adhesive layer between the resin substrate and the first layer. The sealing layer is a resin layer containing resin. The method for determining the stiffness of the sheet in the width direction is as follows. Test pieces with a length of 200 mm and a width of 15 mm were cut from the sheet. The width stiffness of the cut test pieces was measured using a LOOP STIFFNESS TESTER manufactured by Toyo Seiki Co., Ltd. The measurement conditions were set as follows: clamp spacing distance of 100 mm, ring length of 85 mm, and compression speed of 3.3 mm / s. Two test pieces were measured, and the average value of the width stiffness obtained from the two test pieces was taken as the width stiffness of the sheet. It should be noted that when measuring the width stiffness of the sheet, the test pieces were cut with the length of the test piece along the width of the sheet.
Citation Information
Patent Citations
Photosensitive-thermosensitive recording material
JP1993257272A
Polyester resin composition, method of manufacturing the same, polyester film, and solar cell power generation module
JP2011208125A
Power regulation method, computer device, and storage medium
WO2020098248A1
Flexible glass laminate structures for architectural design and other applications
CN106660328A
Pressure measuring sheet
JP2009173307A